COMPLICATIONS OF TRANSSPHENOIDAL APPROACH FOR PITUITARY SURGERY - Dr. Kahtan Adnan Abood; Dr. Hayder Abbas Alkayssi; Dr. Manna Ibrahim Ramadan (Scholar Express Journals, 2022)
This paper aims to study assessment complication Transsphenoidal pituitary surgery where 60 patients collected from different hospitals in Iraq, except for patients who underwent of the pituitary gland tumor. By relying on the electronic record in the hospital to know the immediate complications after pituitary surgery, the patients were divided into three groups Non-functional, Apoplexy, and Macroadenoma patient The main causes of early postoperative complications are hemorrhage in unremoved segments followed by the development of cerebral edema. Disruption of blood circulation in the hypothalamus with the development of hypopituitarism and the causes and nature of postoperative complications also depend on the severity of the patient's condition before surgery, the presence of concomitant diseases
Keywords: Macroadenoma; Non-functional; Transsphenoidal; pituitary tumor